The Collaborative Role of MSMEs and the Blue Economy in Achieving Sustainable Development in Coastal Areas of East Kalimantan - Jumri; Mujanah, Siti; Halik, Abdul (IJESS International Journal of Education and Social Science, 2025)
This research aims to mIdentifying and analyzing collaboration between MSMEs and the blue economy to realize sustainable development in the coastal areas of East Kalimantan.The research was conducted in several regencies in East Kalimantan, namely Balikpapan, Paser, Bontang, Kutai Kartanegara, and East Kutai. These regions were selected because they have significant maritime-based economic activity. Data collection was conducted over a two-month period. This study used a qualitative approach to explore the perceptions, experiences, and views of MSMEs regarding collaboration with the blue economy. The results of this study demonstrate the role ofCollaboration between MSMEs and the blue economy concept not only positively impacts the well-being of coastal communities but also serves as a strategic step towards achieving sustainable development. Strengthening collaboration between MSMEs and the blue economy can become a driving force for sustainable development.